Barcelona towards sustainability / Farah Ayuni Shafie. - Shafie, Farah Ayuni (Universiti Teknologi MARA Cawangan Selangor, 2018)
This paper describes two main aspects of environmental management in Barcelona; city mobility and waste management. The observation is documented through hard evidence of photographs, local authority database and information accessible to the public. This paper is divided into three sections; 1) current urban planning and management 2) the sustainability and environmental approaches governed by the city 3) personal thoughts and experience overlooking the general attitude and culture of the people of Barcelona. The lessons learned can be applied to Malaysia in a organized locality.